Cobalt-based catalyst and preparation method and application thereof
The cobalt-based catalyst prepared by template ion exchange method solves the problems of high cost and complex process for low-concentration CO exhaust gas removal in the prior art, and achieves high efficiency CO removal and high conversion of catalysts, which is suitable for large-scale applications.
Patent Information
- Application Number
- CN202310978071.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-04
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2043-08-04
AI Technical Summary
The prior art has high cost and complex process in the removal of low-concentration CO exhaust gases. It requires adding precipitants during the catalyst preparation process, which is difficult to operate and difficult to achieve large-scale application.
The cobalt-based catalyst was prepared by template ion exchange method, and a mixture containing cobalt hydroxide nanosheets were formed by mixing the second mixture of magnesium hydroxide nanosheets and cobalt salt precursors, and then dried and calcined. The mixture containing 40- was prepared. Cobalt-based catalyst with 60 wt% cobalt element and 0.5-5 wt% magnesium element.
It has achieved efficient CO removal, high CO conversion rate and high catalyst conversion rate. It is suitable for low-concentration CO removal systems, with simple process and strong controllability, and is suitable for large-scale industrial production.
Smart Images

Figure CN119425697A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalyst preparation, and in particular to a cobalt-based catalyst and a preparation method and application thereof. Background Art
[0002] Many processes in industrial production will produce CO-rich gases, such as coal gasification, coke oven gas, blast furnace gas and converter gas in steel production. The CO concentration in these gases is high (>5vol%), and direct emission will cause huge waste of resources and serious environmental pollution. Therefore, methods such as cryogenic separation, solvent recovery and solid adsorption separation are usually used to purify, separate and purify CO. The CO content of the purified gas is very low and can be directly discharged in compliance with the emission standards.
[0003] However, there are some other processes in which the CO concentration in the tail gas produced during production is low (<5000ppm), such as the analytical gas from the low-temperature methanol washing device used for acid gas removal in the coal gasification unit. For this type of tail gas, the recovery cost is high. In order to meet the emission requirements, adsorption, photocatalysis, low-temperature plasma conversion, combustion and other methods are usually used to remove CO in it to meet the emission requirements. Among them, the catalytic oxidation method introduces a high-efficiency catalyst on the basis of the combustion method to reduce the temperature of the combustion process. It has the advantages of simple process and high removal efficiency, and therefore has received widespread attention.
[0004] Common precious metal catalysts are widely used for CO tail gas removal, but cheap non-precious metal-based catalysts can greatly reduce the cost for this reaction and are therefore more attractive.
[0005] For example, CN109621972A provides a method using CuMnO x Catalytic elimination of CO: CO begins to be oxidized to CO at 30°C 2 , which is completely oxidized to CO at 108-115℃ 2 The temperature at which 50% of CO is oxidized is 65-70°C, but the preparation method still requires the addition of ammonium oxalate as a precipitant, and the process is complicated.
[0006] CN113145164A discloses a method for preparing a Cu@HS hollow structure molecular sieve for CO removal. A Cu-Silicalite solid structure molecular sieve is prepared using a Silicalite solid structure molecular sieve, and then mixed with deionized water through TPAOH. Under reduced pressure and suction filtration, the solution is dripped into the impregnated sample Cu-Silicalite. The Cu@HS hollow structure molecular sieve is used in the catalytic cracking flue gas of a refinery, and the CO removal rate is 100%. However, since the molecular sieve needs to be synthesized, organic wastewater that pollutes the environment will be generated during the preparation process, and the molecular sieve preparation process is difficult to scale up.
[0007] CN115430431A discloses a Mn-doped Co-based catalyst and its preparation method and application. The prior art adds a suitable proportion of cobalt salt and manganese salt to a magnesium oxide solution, stirs for 1-2 hours to obtain a precipitate, washes the precipitate to a pH value of 6.5-7.5; dries at 60-80°C for 10-15 hours, then heats to 500-600°C at a heating rate of 1-5°C / min, and calcines at 500-600°C for 1-3 hours to obtain a Mn-doped Co-based catalyst. The porous nanosheet catalyst prepared by the prior art increases the contact area between the soot and the catalyst, so that the active area of the catalyst is effectively utilized. However, a precipitant still needs to be added in the preparation process to adjust the pH value, which is difficult to operate, making its large-scale application a problem. Summary of the invention
[0008] The purpose of the present invention is to provide a cobalt-based catalyst with high CO removal rate, high catalyst conversion rate and suitable for low-concentration CO removal system.
[0009] In order to achieve the above object, the first aspect of the present invention provides a cobalt-based catalyst, which contains 40-60wt% of cobalt and 0.5-5wt% of magnesium; the cobalt-based catalyst has an oxygen vacancy content of 15-60% and a specific surface area of 50-200m 2 / g.
[0010] The second aspect of the present invention provides a method for preparing the cobalt-based catalyst described in the first aspect, comprising the following steps:
[0011] (1) In the presence of water, magnesium hydroxide nanosheets and a cobalt salt precursor are mixed for a second time to obtain a mixture I containing cobalt hydroxide nanosheets; the second mixing time is 2-30 hours; the molar ratio of the cobalt element in the cobalt salt precursor to the magnesium element in the magnesium hydroxide nanosheets is 1:0.5-3 in terms of metal elements; the average thickness of the magnesium hydroxide nanosheets is 1-10 nm, and the specific surface area is 100-500 m 2 / g;
[0012] (2) drying the mixture I to obtain a mixture II;
[0013] (3) subjecting the mixture II to a second calcination treatment to obtain the cobalt-based catalyst; the conditions of the second calcination treatment include: a temperature of 200-800° C., a heating rate of 2-20° C. / min, and a time of 2-4 h.
[0014] The third aspect of the present invention provides a cobalt-based catalyst prepared by the method described in the second aspect.
[0015] The fourth aspect of the present invention provides use of the cobalt-based catalyst described in the first aspect or the third aspect in the treatment of CO-containing gas.
[0016] The present invention provides a non-precious metal catalyst with a simple and controllable preparation process for the efficient removal of CO tail gas in the petrochemical production process, and invents a method for preparing a catalyst by template ion exchange and without a precipitant, which regulates the number of oxygen vacancies on the catalyst surface, promotes the dispersion of active metals and the exposure of active metal sites; and then adjusts the optimal roasting temperature, controls the particle size of the catalyst particles, and efficiently constructs catalytic active sites on the catalyst surface. The method provided by the present invention enables the active metal precursor and the carrier to fully fuse and change each other, construct more doped oxygen vacancies to adsorb and activate CO, and improve the catalytic performance of the catalyst.
[0017] The present invention uses an ion exchange method to use the precursor ultra-thin magnesium hydroxide as a template, and forms ultra-thin cobalt hydroxide nanosheets in situ through the difference in solubility product, and then obtains a cobalt-based catalyst through calcination. The catalyst surface defect sites are efficiently constructed by regulating the concentration of the salt solution and the calcination temperature, which promotes the adsorption and activation of the substrate, has high catalytic oxidation efficiency, low removal temperature, and less energy consumption.
[0018] Compared with the prior art, the preparation method of the cobalt-based catalyst provided by the present invention has simple process, is green and environmentally friendly, has strong controllability, is more suitable for industrial large-scale production, and has good application prospects.
[0019] The coprecipitation method used in the prior art to prepare cobalt-based catalysts requires the addition of an additional precipitant and strict control of the pH value, which is complex to operate. The technical solution provided by the present invention can controllably prepare cobalt-based catalysts to obtain catalysts with smaller active component particle size, higher catalytic activity, and longer catalyst life. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 is a transmission electron microscope image of magnesium hydroxide nanosheets in Example 1;
[0021] Figure 2 is a transmission electron microscope image of magnesium hydroxide nanosheets in Example 1;
[0022] Figure 3 is a transmission electron microscope image of cobalt hydroxide nanosheets in Example 1;
[0023] Figure 4 is a transmission electron microscope image of the cobalt-based catalyst of Example 1;
[0024] Figure 5 It is the X-ray diffraction (XRD) pattern of the cobalt-based catalyst in Example 1. DETAILED DESCRIPTION
[0025] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0026] As mentioned above, the first aspect of the present invention provides a cobalt-based catalyst, which contains 40-60wt% of cobalt and 0.5-5wt% of magnesium; the cobalt-based catalyst has an oxygen vacancy content of 15-60% and a specific surface area of 50-200m 2 / g.
[0027] Preferably, the cobalt-based catalyst contains 50-60 wt% of cobalt and 0.5-2 wt% of magnesium.
[0028] Preferably, the cobalt-based catalyst has an oxygen vacancy content of 20-60% and a specific surface area of 50-200 m 2 / g.
[0029] In the present invention, the cobalt element and the magnesium element are both present in the cobalt-based catalyst in the form of oxides.
[0030] Preferably, the average particle diameter of the cobalt-based catalyst is 1-20 nm, preferably 1-10 nm.
[0031] The cobalt-based catalyst provided by the present invention has a highly efficient catalytic effect on raw gas with a CO concentration of ≤5v%, a reaction mass space velocity of 60000mL / g / h, a CO conversion rate of ≥1% at above 50°C, a CO conversion rate of ≥99% at above 230°C, stability of ≥300h, and can make the residual CO volume concentration in the raw gas ≤50ppm after the reaction.
[0032] As mentioned above, the second aspect of the present invention provides a method for preparing the cobalt-based catalyst described in the first aspect, comprising the following steps:
[0033] (1) In the presence of water, magnesium hydroxide nanosheets and a cobalt salt precursor are mixed for a second time to obtain a mixture I containing cobalt hydroxide nanosheets; the second mixing time is 2-30 hours; the molar ratio of the cobalt element in the cobalt salt precursor to the magnesium element in the magnesium hydroxide nanosheets is 1:0.5-3 in terms of metal elements; the average thickness of the magnesium hydroxide nanosheets is 1-10 nm, and the specific surface area is 100-500 m 2 / g;
[0034] (2) drying the mixture I to obtain a mixture II;
[0035] (3) subjecting the mixture II to a second calcination treatment to obtain the cobalt-based catalyst; the conditions of the second calcination treatment include: a temperature of 200-800° C., a heating rate of 2-20° C. / min, and a time of 2-4 h.
[0036] pass Figure 1 and Figure 2 It can be seen from the transmission electron microscope image of the magnesium hydroxide nanosheet shown that the magnesium hydroxide nanosheet of the present invention is in an irregular sheet shape. The inventors of the present invention have found in their research that the cobalt-based catalyst prepared by using the magnesium hydroxide nanosheet of this size as a template and in combination with the other technical features of the present invention has a more excellent catalytic performance.
[0037] Preferably, the method further comprises: first mixing the magnesium oxide particles with water to obtain magnesium hydroxide nanosheets; the conditions of the first mixing include: a stirring rate of 70-150 rpm, a temperature of 18-40° C., and a time of 10 min to 24 h.
[0038] Preferably, the amount of the magnesium oxide particles used is such that the initial concentration of magnesium in the reaction system formed by the first mixing is 1.0-1.5 mol / L.
[0039] Preferably, the magnesium oxide particles are obtained by subjecting a magnesium precursor to a first calcination treatment; and the average particle diameter of the magnesium oxide particles is 5-30 nm.
[0040] According to a preferred specific implementation manner, the conditions of the first calcination treatment include: a temperature of 600-1000° C., a heating rate of 2-20° C. / min, a time of 2-4 h, and an air flow rate of 10-100 mL / min.
[0041] Preferably, the magnesium precursor is selected from at least one of light magnesium oxide, basic magnesium carbonate, and magnesium chloride hexahydrate.
[0042] According to a preferred specific embodiment, the magnesium precursor is basic magnesium carbonate and / or magnesium chloride hexahydrate, and the second mixing time in step (1) is 2-5 hours. The inventors of the present invention have found in their research that the use of basic magnesium carbonate and / or magnesium chloride hexahydrate as a magnesium precursor can significantly shorten the reaction time of the second mixing and improve the production efficiency of the cobalt-based catalyst.
[0043] According to another preferred embodiment, the magnesium precursor is light magnesium oxide, and the second mixing time in step (1) is 20-30 hours. The inventors of the present invention have found in their research that the cobalt-based catalyst prepared by using light magnesium oxide as a magnesium precursor has better catalytic performance.
[0044] In the present invention, after the solid-liquid mixture containing magnesium hydroxide nanosheets is obtained by the first mixing, the cobalt salt precursor can be directly introduced into the second mixing, or the solid-liquid mixture containing magnesium hydroxide nanosheets can be sequentially washed, filtered, dried, etc. to obtain the magnesium hydroxide nanosheets, and then the magnesium hydroxide nanosheets are used to participate in the second mixing. The present invention will not be repeated here, and those skilled in the art should not be understood as limiting the present invention.
[0045] The magnesium hydroxide nanosheets obtained by the present invention may also contain the magnesium oxide particles that have not reacted completely. When participating in the second mixing in step (1), the magnesium hydroxide nanosheets that have not reacted completely can continue to react to obtain magnesium hydroxide nanosheets. At the same time, the magnesium hydroxide nanosheets are used as templates and the cobalt hydroxide nanosheets are formed in situ by an ion exchange method using the difference in solubility product.
[0046] pass Figure 3 It can be seen from the transmission electron microscope image of the cobalt hydroxide nanosheet shown in that the cobalt hydroxide nanosheet described in the present invention is in an irregular sheet shape.
[0047] Preferably, in step (1), the molar ratio of the cobalt element in the cobalt salt precursor to the magnesium element in the magnesium hydroxide nanosheets is 1:1-2.
[0048] Preferably, in step (1), the amount of the cobalt salt precursor is such that the initial concentration of the cobalt element in the reaction system formed by the second mixing is 0.1-2 mol / L, more preferably 0.4-0.8 mol / L. The inventors have found that under this more preferred condition, the CO removal rate and catalyst conversion rate of the cobalt-based catalyst obtained by the present invention are higher.
[0049] Preferably, in step (1), the cobalt salt precursor is selected from at least one of cobalt nitrate hexahydrate, cobalt chloride hexahydrate, cobalt acetate tetrahydrate, and cobalt sulfate heptahydrate.
[0050] More preferably, in step (1), the cobalt salt precursor is cobalt nitrate hexahydrate. The inventors of the present invention have found in their research that, compared with other water-soluble cobalt salts, the cobalt-based catalyst prepared by selecting cobalt nitrate hexahydrate as the cobalt salt precursor has better catalytic activity and higher CO conversion rate.
[0051] Preferably, in step (1), the second mixing conditions include: a stirring rate of 70-150 rpm, a temperature of 18-40° C., and a time of 2-30 h.
[0052] Preferably, in step (2), the drying treatment is carried out at a temperature of 20-50°C, preferably 20-30°C, and for a period of 20-26 hours.
[0053] According to a preferred specific embodiment, in step (3), the conditions of the second calcination treatment include: a temperature of 200-400°C, a heating rate of 2-10°C / min, a time of 2-3h, and an air flow rate of 10-100mL / min. The inventors of the present invention have found in their research that under the preferred second calcination treatment conditions, the CO removal rate and catalyst conversion rate of the cobalt-based catalyst provided by the present invention are higher, and the catalytic performance is more excellent.
[0054] As mentioned above, the third aspect of the present invention provides a cobalt-based catalyst prepared by the method described in the second aspect.
[0055] from Figure 4 It can be seen from the transmission electron microscope image of the cobalt-based catalyst that the cobalt-based catalyst particles provided by the present invention have a small particle size and uniform size and have a higher specific surface area.
[0056] Figure 5 is the XRD spectrum of the cobalt-based catalyst, where 2-theta is the angle of 2θ at which the x-ray diffractometer scans the entire diffraction area, which exists as the angle change and as the horizontal coordinate of the x-ray diffraction spectrum. Figure 5 It can be seen from the XRD spectrum that the cobalt-based catalyst provided by the present invention exhibits Co 3 O 4 Obvious diffraction peaks.
[0057] Since the magnesium content in the cobalt-based catalyst of the present invention does not reach the detection limit of XRD, the present invention uses inductively coupled plasma technology (ICP) to detect the magnesium content in the cobalt-based catalyst.
[0058] As mentioned above, the fourth aspect of the present invention provides the use of the cobalt-based catalyst described in the first aspect or the third aspect in the treatment of CO-containing gas.
[0059] Preferably, the concentration of CO in the CO-containing gas is ≤5v%.
[0060] The present invention will be described in detail below by way of examples. In the following examples, unless otherwise specified, the raw materials are all commercially available.
[0061] In the following examples, the specific surface areas of magnesium hydroxide nanosheets and cobalt-based catalysts were determined by nitrogen adsorption-desorption method.
[0062] In the following examples, an XPS ray photoelectron spectrometer (manufacturer: Thermo Fisher Scientific, model: Thermo Kalpha) was used to test the oxygen vacancy content of the cobalt-based catalyst.
[0063] Example 1
[0064] (1) The magnesium precursor was first calcined at 750°C for 2 h at an air flow rate of 30 mL / min and a heating rate of 5°C / min to obtain magnesium oxide particles (with an average particle diameter of 20 nm). The magnesium oxide particles were first mixed with water at 80 rpm and 25°C for 24 h, and then washed, filtered, and dried to obtain magnesium hydroxide nanosheets (with an average thickness of 3 nm and a specific surface area of 250 m 2 / g);
[0065] The magnesium precursor is basic magnesium carbonate; the amount of magnesium oxide particles used is 0.0125 mol, and the amount of magnesium oxide particles used is such that in the first mixed system, the initial concentration of magnesium element is 1.25 mol / L;
[0066] (2) in the presence of water, mixing all the magnesium hydroxide nanosheets obtained in step (1) with the cobalt salt precursor at 100 rpm and 25° C. for a second time for 3 h to obtain a mixture I containing cobalt hydroxide nanosheets;
[0067] The cobalt salt precursor is cobalt nitrate hexahydrate, and the amount used is 0.0125 mol. The amount of the cobalt salt precursor is such that in the reaction system formed by the second mixture, the initial concentration of the cobalt element is 0.5 mol / L (in terms of metal elements, the molar ratio of the cobalt element in the cobalt salt precursor to the magnesium element in the magnesium hydroxide nanosheets is 1:1);
[0068] (3) drying the mixture I at 25° C. for 24 h to obtain a mixture II;
[0069] (4) The mixture II was subjected to a second calcination treatment at 300° C. for 2 h at an air flow rate of 50 mL / min and a heating rate of 3° C. / min to obtain a cobalt-based catalyst.
[0070] Example 2
[0071] (1) The magnesium precursor was first calcined at 750°C for 2 h at an air flow rate of 50 mL / min and a heating rate of 3°C / min to obtain magnesium oxide particles (with an average particle diameter of 25 nm). The magnesium oxide particles were first mixed with water at 120 rpm and 25°C for 24 h, and then washed, filtered, and dried to obtain magnesium hydroxide nanosheets (with an average thickness of 2 nm and a specific surface area of 170 m 2 / g);
[0072] The magnesium precursor is light magnesium oxide; the amount of magnesium oxide particles used is 0.0125 mol, and the amount of magnesium oxide particles used is such that the initial concentration of magnesium in the first mixed system is 1.25 mol / L;
[0073] (2) in the presence of water, mixing all the magnesium hydroxide nanosheets obtained in step (1) with the cobalt salt precursor at 80 rpm and 25° C. for a second time for 24 hours to obtain a mixture I containing cobalt hydroxide nanosheets;
[0074] The cobalt salt precursor is cobalt nitrate hexahydrate, and the amount used is 0.0125 mol. The amount of the cobalt salt precursor is such that in the reaction system formed by the second mixture, the initial concentration of the cobalt element is 0.5 mol / L (in terms of metal elements, the molar ratio of the cobalt element in the cobalt salt precursor to the magnesium element in the magnesium hydroxide nanosheets is 1:1);
[0075] (3) drying the mixture I at 25° C. for 24 h to obtain a mixture II;
[0076] (4) The mixture II was subjected to a second calcination treatment at an air flow rate of 30 mL / min, a heating rate of 7° C. / min, and 200° C. for 3 h to obtain a cobalt-based catalyst.
[0077] Example 3
[0078] (1) The magnesium precursor was first calcined at 750°C for 2 h at an air flow rate of 30 mL / min and a heating rate of 5°C / min to obtain magnesium oxide particles (with an average particle diameter of 25 nm). The magnesium oxide particles were first mixed with water at 75 rpm and 28°C for 24 h, and then washed, filtered, and dried to obtain magnesium hydroxide nanosheets (with an average thickness of 3 nm and a specific surface area of 250 m 2 / g);
[0079] The magnesium precursor is magnesium chloride hexahydrate; the amount of magnesium oxide particles used is 0.0125 mol, and the amount of magnesium oxide particles used is such that the initial concentration of magnesium in the first mixed system is 1.25 mol / L;
[0080] (2) in the presence of water, mixing all the magnesium hydroxide nanosheets obtained in step (1) with the cobalt salt precursor at 100 rpm and 28° C. for a second time for 3 h to obtain a mixture I containing cobalt hydroxide nanosheets;
[0081] The cobalt salt precursor is cobalt chloride hexahydrate, and the amount used is 0.0125 mol. The amount of the cobalt salt precursor is such that in the reaction system formed by the second mixture, the initial concentration of the cobalt element is 0.5 mol / L (in terms of metal element, the molar ratio of the cobalt element in the cobalt salt precursor to the magnesium element in the magnesium hydroxide nanosheet is 1:1);
[0082] (3) drying the mixture I at 28° C. for 24 h to obtain a mixture II;
[0083] (4) The mixture II was subjected to a second calcination treatment at 400° C. for 2 h at an air flow rate of 50 mL / min and a heating rate of 3° C. / min to obtain a cobalt-based catalyst.
[0084] Example 4
[0085] This embodiment is carried out using a process similar to that of Embodiment 1, except that in step (2), the amount of the cobalt salt precursor used in this embodiment is such that the initial concentration of the cobalt element in the second mixed reaction system is 0.2 mol / L, and the type and amount of the cobalt salt precursor remain unchanged;
[0086] A cobalt-based catalyst is prepared.
[0087] Example 5
[0088] This embodiment adopts a process similar to that of embodiment 1, except that in step (4), the temperature of the second calcination treatment adopted in this embodiment is adjusted from 300° C. to 500° C., and the other conditions remain unchanged;
[0089] A cobalt-based catalyst is prepared.
[0090] Example 6
[0091] This embodiment adopts a process similar to that of Embodiment 2, except that this embodiment does not perform the first roasting treatment, and directly uses light magnesium oxide to participate in the first mixing, specifically:
[0092] (1) Light magnesium oxide and water were first mixed at 75 rpm and 25° C. for 24 h, and then washed, filtered, dried, and other steps to obtain magnesium hydroxide nanosheets (average thickness of 2 nm and specific surface area of 225 m 2 / g);
[0093] The dosage of light magnesium oxide is 0.0125 mol, and the initial concentration of light magnesium oxide in the first mixed system is 1.25 mol / L;
[0094] (2) in the presence of water, mixing all the magnesium hydroxide nanosheets obtained in step (1) with the cobalt salt precursor at 100 rpm and 25° C. for a second time for 24 hours to obtain a mixture I containing cobalt hydroxide nanosheets;
[0095] The cobalt salt precursor is cobalt nitrate hexahydrate, and the amount used is 0.0125 mol. The amount of the cobalt salt precursor is such that in the reaction system formed by the second mixture, the initial concentration of the cobalt element is 0.5 mol / L (in terms of metal elements, the molar ratio of the cobalt element in the cobalt salt precursor to the magnesium element in the magnesium hydroxide nanosheets is 1:1);
[0096] (3) drying the mixture I at 25° C. for 24 h to obtain a mixture II;
[0097] (4) The mixture II was subjected to a second calcination treatment at 200° C. for 3 h at an air flow rate of 50 mL / min and a heating rate of 3° C. / min to obtain a cobalt-based catalyst.
[0098] Example 7
[0099] This embodiment adopts a process similar to that of embodiment 1, except that in step (3), the drying temperature is adjusted from 25°C to 60°C, and the other conditions remain unchanged;
[0100] A cobalt-based catalyst is prepared.
[0101] Example 8
[0102] This example is carried out using a process similar to that of Example 1, except that in step (2), the cobalt salt precursor cobalt nitrate hexahydrate is replaced with cobalt acetate tetrahydrate; specifically:
[0103] Step (2): In the presence of water, all the magnesium hydroxide nanosheets obtained in step (1) are mixed with the cobalt salt precursor at 100 rpm and 25° C. for a second time for 3 hours to obtain a mixture I containing cobalt hydroxide nanosheets;
[0104] The cobalt salt precursor is cobalt acetate tetrahydrate, and the amount used is 0.0125 mol. The amount of the cobalt salt precursor is such that in the second mixed reaction system, the initial concentration of cobalt element is 0.1 mol / L (in terms of metal element, the molar ratio of cobalt element in the cobalt salt precursor to magnesium element in the magnesium hydroxide nanosheets is 1:1).
[0105] The rest remain unchanged to prepare a cobalt-based catalyst.
[0106] Comparative Example 1
[0107] This comparative example was carried out using a process similar to that of Example 1, except that in step (4), the temperature of the second calcination treatment was adjusted from 300° C. to 900° C., and the other conditions remained unchanged;
[0108] A cobalt-based catalyst is prepared.
[0109] Comparative Example 2
[0110] Co was prepared by coprecipitation method 3 O 4 catalyst
[0111] 8.58g of magnesium acetate tetrahydrate and 4.24g of anhydrous sodium carbonate are dissolved in 400ml and 100ml of deionized water respectively to form an aqueous solution with a concentration ratio of 1:4, and then the sodium carbonate solution is poured into the magnesium acetate solution and mixed and stirred for 10 minutes to obtain a magnesium hydroxide precipitate. After the magnesium hydroxide precipitate is centrifuged once, water is added twice and ethanol is added once and then centrifuged and washed again to make its pH 7, and finally dried at 60°C for 12h and heated to 500°C at a heating rate of 2°C / min; calcined at 500°C for 2h to form magnesium oxide.
[0112] Take 0.04g magnesium oxide and dissolve it in deionized water and add 20mL of 0.05mol / L cobalt nitrate solution, stir for 1.5h, then filter (or centrifuge) and wash with water and ethanol again to make its pH 7, then dry at 60℃ for 12h, and heat to 500℃ at a heating rate of 2℃ / min, calcine at 500℃ for 2h, and finally obtain Co 3 O 4 catalyst.
[0113] The composition and parameter characteristics of the cobalt-based catalysts prepared in each example are shown in Table 1.
[0114] Table 1
[0115]
[0116] Test Example 1
[0117] The catalytic CO reaction was tested on a fixed bed. The specific test process is as follows:
[0118] 0.7g of the cobalt-based catalyst of the present invention was taken for CO catalytic oxidation reaction, which was carried out on a micro-fixed bed evaluation device-gas chromatography online analysis integrated system device. The cobalt-based catalyst tablet was sieved, and the catalyst particles (0.4-0.85mm) were selected and loaded into a stainless steel reaction tube with a quartz liner, switched to the required reaction temperature, and CO and air mixed raw gas were introduced respectively for reaction, wherein the CO concentration in the raw gas was 5v%, the mass space velocity was 60000mL / g / h, and the reaction temperature was controlled by heating. During the reaction, after each temperature point was stable for 30min, the chromatographic sampling was carried out for online analysis.
[0119] The cobalt-based catalyst provided by the present invention has a high catalytic effect on the raw gas with a CO concentration of ≤5v%, the reaction mass space velocity is 60000mL / g / h, the CO conversion rate is ≥1% above 50°C, and the CO conversion rate is ≥99% above 230°C. The present invention exemplarily provides data as shown in Table 2 to illustrate the catalytic effect of the cobalt-based catalyst prepared in Example 2.
[0120] CO conversion rate (%) = (volume flow rate of CO in the raw gas - volume flow rate of CO in the tail gas after reaction) / volume flow rate of CO in the raw gas × 100%
[0121] Table 2
[0122] Temperature(℃) CO conversion rate (%) 50 1.2 100 21.3 125 54.0 150 98.6 175 100 200 100
[0123] It can be seen from the data in Table 2 that the catalyst prepared by this method has very good low-temperature activity.
[0124] Test Example 2
[0125] The cobalt-based catalysts prepared in the examples and comparative examples were used to carry out CO catalytic oxidation reaction. The specific test process is as follows:
[0126] Take 0.35g of the cobalt-based catalyst prepared in each example to carry out CO catalytic oxidation reaction, which is carried out on a micro-fixed bed evaluation device gas chromatography online analysis integrated system device. The cobalt-based catalyst tablets are sieved, and the catalyst particles (0.4-0.85mm) are selected and loaded into a stainless steel reaction tube with a quartz liner, switched to the required reaction temperature, and CO and air mixed raw gas are introduced respectively for reaction, wherein the CO concentration in the raw gas is 5v%, the reaction mass space velocity is 60000mL / g / h, and the reaction temperature is controlled by heating. During the reaction, after each temperature point is stable for 30min, the chromatographic sampling is carried out for online analysis.
[0127] CO conversion rate (%) = (volume flow rate of CO in the raw gas - volume flow rate of CO in the tail gas after reaction) / volume flow rate of CO in the raw gas × 100%
[0128] The cobalt-based catalysts prepared in each embodiment and comparative example were used to carry out CO catalytic oxidation reaction, and the T 50 and T 90 Value, T 50 , T 90 They respectively represent the temperature corresponding to a CO conversion rate of 50% and the temperature corresponding to a CO conversion rate of 90%.
[0129] The results are shown in Table 3.
[0130] Table 3
[0131] <![CDATA[T 50 (℃)]]> <![CDATA[T 90 (℃)]]> Example 1 122 141 Example 2 120 138 Example 3 151 162 Example 4 125 150 Example 5 160 181 Example 6 135 156 Example 7 125 150 Example 8 150 171 Comparative Example 1 197 293 Comparative Example 2 191 218
[0132] It can be seen from the data in Table 3 that when the cobalt-based catalyst obtained by the technical solution provided by the present invention is used for CO catalytic oxidation, T 50 and T 90The value is lower, and the temperature of the second calcination has a significant effect on the performance of the cobalt-based catalyst. A lower calcination temperature is conducive to the synthesis of catalysts with smaller particle sizes and significantly better catalytic performance.
[0133] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A cobalt-based catalyst, characterized in that The cobalt-based catalyst contains 40-60wt% of cobalt and 0.5-5wt% of magnesium. The cobalt-based catalyst has an oxygen vacancy content of 15-60% and a specific surface area of 50-200 m 2 / g.
2. The cobalt-based catalyst according to claim 1, wherein The average particle diameter of the cobalt-based catalyst is 1-20 nm.
3. A method for preparing the cobalt-based catalyst according to claim 1 or 2, characterized in that: The following steps are involved: (1) In the presence of water, magnesium hydroxide nanosheets and a cobalt salt precursor are mixed for a second time to obtain a mixture I containing cobalt hydroxide nanosheets; the second mixing time is 2-30 hours; the molar ratio of the cobalt element in the cobalt salt precursor to the magnesium element in the magnesium hydroxide nanosheets is 1:0.5-3 in terms of metal elements; the average thickness of the magnesium hydroxide nanosheets is 1-10 nm, and the specific surface area is 100-500 m 2 / g; (2) drying the mixture I to obtain a mixture II; (3) subjecting the mixture II to a second calcination treatment to obtain the cobalt-based catalyst; The conditions of the second calcination treatment include: temperature of 200-800° C., heating rate of 2-20° C. / min, and time of 2-4 h.
4. The method according to claim 3, wherein: The method also includes: first mixing magnesium oxide particles with water to obtain magnesium hydroxide nanosheets; the conditions of the first mixing include: a stirring rate of 70-150 rpm, a temperature of 18-40° C., and a time of 10 min to 24 h.
5. The method according to claim 4, wherein: The magnesium oxide particles are obtained by subjecting a magnesium precursor to a first calcination treatment; the average particle diameter of the magnesium oxide particles is 5-30 nm.
6. The method according to claim 5, wherein: The conditions of the first calcination treatment include: temperature of 600-1000° C., heating rate of 2-20° C. / min, time of 2-4 hours, and air flow rate of 10-100 mL / min.
7. The method according to claim 5 or 6, wherein: The magnesium precursor is selected from at least one of light magnesium oxide, basic magnesium carbonate, and magnesium chloride hexahydrate.
8. The method according to any one of claims 3 to 7, wherein: In step (1), the amount of the cobalt salt precursor used is such that the initial concentration of the cobalt element in the reaction system formed by the second mixing is 0.1-2 mol / L.
9. The method according to any one of claims 3 to 8, wherein: In step (1), the cobalt salt precursor is selected from at least one of cobalt nitrate hexahydrate, cobalt chloride hexahydrate, cobalt acetate tetrahydrate, and cobalt sulfate heptahydrate; Preferably, the cobalt salt precursor is cobalt nitrate hexahydrate.
10. The method according to any one of claims 3 to 9, wherein: In step (1), the second mixing conditions include: a stirring rate of 70-150 rpm, a temperature of 18-40° C., and a time of 2-30 h.
11. The method according to any one of claims 3 to 10, wherein: In step (2), the drying process is carried out at a temperature of 20-50°C and for a time of 20-26 hours.
12. The method according to any one of claims 3 to 11, wherein: In step (3), the conditions of the second calcination treatment include: temperature of 200-400°C, heating rate of 2-10°C / min, time of 2-3h, and air flow rate of 10-100mL / min.
13. A cobalt-based catalyst prepared by the method according to any one of claims 3 to 12.
14. Use of the cobalt-based catalyst according to any one of claims 1 to 2 and 13 in the treatment of CO-containing gas; Preferably, the concentration of CO in the CO-containing gas is ≤5v%.
Citation Information
Patent Citations
High-activity and high-stability catalyst for catalytic oxidation of CO and preparation method of high-activity and high stability catalyst
CN107876097A
Preparation method of cobalt oxide rich in oxygen vacancy for electrocatalytic water desorption and oxygen desorption
CN113106486A
Cobalt oxide catalyst based on cation doping and preparation method and application thereof
CN114984960A
Cobalt-based perovskite oxide catalyst and preparation and application thereof
CN116459840A
A humidifier using heater with rapid atomizing function
KR102636833B1